2019
DOI: 10.1088/1361-6641/aafc86
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of short channel characteristics in graded channel dual-material elliptical gate-all-around (GC DM EGAA) MOSFET

Abstract: A comprehensive investigation of the subthreshold behavior of a graded channel dual-material elliptical gate-all-around MOSFET has been presented in this research. Detailed analysis of the device's immunity over the various short channel effects like threshold voltage roll-off, draininduced barrier lowering, subthreshold swing and hot carrier effect have been conducted using the central potential where the latter has been derived using the quasi-3-D scaling length concept. The analytical results have been veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Figure 2(a) shows the calibration of the simulation setup with the experimental results of [31] at V GS = 1 and 0.1 V, in both linear and logarithmic scale. Figure 2(b) demonstrates validation of our proposed model with that of the device model proposed for JLAMSG MOSFET in [4], JLDMCSG MOSFET in [6] and Circular GCDMG MOS-FET in [9]. Therefore our numerical simulations match well with experimental results and our proposed analytical model matches well with other reported analytical models.…”
Section: Simulation Setupsupporting
confidence: 77%
See 4 more Smart Citations
“…Figure 2(a) shows the calibration of the simulation setup with the experimental results of [31] at V GS = 1 and 0.1 V, in both linear and logarithmic scale. Figure 2(b) demonstrates validation of our proposed model with that of the device model proposed for JLAMSG MOSFET in [4], JLDMCSG MOSFET in [6] and Circular GCDMG MOS-FET in [9]. Therefore our numerical simulations match well with experimental results and our proposed analytical model matches well with other reported analytical models.…”
Section: Simulation Setupsupporting
confidence: 77%
“…For figure 3(b) it could be observed that the electric field at drain end increases with L 1 : L 2 , (increase in HCEs). Therefore, SCEs decreases and HCEs increase with L 1 :L 2 [9]. Thus for further comparisons, we have optimized L 1 :L 2 to 1:1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations